О влиянии озона на характеристики коронного разряда в воздухе - Блага, А.В.; Божко, И.В.; Бржезицкий, В.А. (Технічна електродинаміка, 2012)
The influence of the ozone as well as the humidity and air pressure on the current and voltage corona discharge in gap "wirecylinder" is studying. It is shown that negative corona discharge compared with positive is more sensitive to changing parameters of the gas environment. Increasing partial pressures of water vapor and ozone in the air makes more voltage and lower current of corona discharge. The sensitivity of current and voltage negative corona with respect to the partial pressure of ozone is above 10 time more than one of water.